A study on pain management of renal colic patient in emergency department: the association factors of patient satisfaction - Ramli, Mohd Khairulizwan (2015)
INTRODUCTION : Renal colic pain is one of the commonest severe pain that presented to emergency department. However there are no exact studies to determine about the effectiveness of pain management and associated factors of patient satisfaction on pain management of renal colic patients. OBJECTIVES : There are 4 specific objectives in this study. The first is to determine the sociodemographic factor for suspected acute renal colic patients. The second is to determine the mean pain score of patient presented to emergency department. The third is to determine the associated factors of patient satisfaction on pain management of renal colic patients precisely on sociodemographic variables and the last is to compare effectiveness of suspected acute renal colic pain management between HUSM and HSNZ METHODOLOGY : This is a cross-sectional study conducted in emergency department of Hospital Sultanah Nurzahirah, HSNZ Kuala Terengganu and Hospital Universiti Sains Malaysia HUSM Kubang Kerian from September 2013 to June 2014 using a questionnaire comprised of sociodemographic and several dependent variables. The patient were asked about the pain score during arrival and after treatment during management of acute renal colic pain.. The test that was used is chi square, simple and multiple linear regression and independent t-test. RESULTS: : A total of 245 patients were enrolled in this study. The mean pain score from patients including all variables was 8.09 + 0.974. Based on Multiple Linear Regression analysis, the factors for satisfaction in services received was Sex (p=0.029). Race was not involve in statistical analysis to avoid bias due to malay is the majority participants in this study. No other sociodemographic factors showed correlation with other satisfaction measures. There was a significant difference of pain management between HUSM and HSNZ (p=0.011). CONCLUSION: Since the sociodemographic variables seems to be weakly related to patient satisfaction, some of the findings are not following the previous study about sociodemographic variables as association factors to patient satisfaction. So, there is a need for further study for evaluation of other association factors of patient satisfaction on pain management of renal colic patients for benefits of the patient.